2009
DOI: 10.3945/ajcn.2008.26862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of micronutrients on growth of children under 5 y of age: meta-analyses of single and multiple nutrient interventions

Abstract: Our findings confirm earlier results of no benefits for interventions including iron and vitamin A only but differ from the earlier meta-analysis that found improvements in linear growth for zinc only interventions. This may be due to the improved nutritional status of children in the more recent studies. Multiple micronutrient interventions improve linear growth, but the benefits are small. Other strategies are needed to prevent stunting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
152
3
21

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(183 citation statements)
references
References 93 publications
7
152
3
21
Order By: Relevance
“…Estudos sobre a suplementação de zinco têm mostrado efeitos positivos sobre os desfechos clínicos e o crescimento, especialmente entre crianças com o crescimento afetado 31,32 . Hambidge et al 22 consideraram que a necessidade de zinco para crianças com doença hepática deveria ser cerca de 40% maior do que aquela considerada para crianças saudáveis.…”
Section: Discussionunclassified
“…Estudos sobre a suplementação de zinco têm mostrado efeitos positivos sobre os desfechos clínicos e o crescimento, especialmente entre crianças com o crescimento afetado 31,32 . Hambidge et al 22 consideraram que a necessidade de zinco para crianças com doença hepática deveria ser cerca de 40% maior do que aquela considerada para crianças saudáveis.…”
Section: Discussionunclassified
“…25 Trials of zinc supplementation have shown positive effects on clinical outcomes and growth, especially among children who are stunted. 31,32 Hambidge et al, 22 studying children with biliary atresia, considered that the zinc requirement for net absorption would be 40% greater than that of healthy infants. Considering that the liver impairment affects the zinc metabolism and absorption of dietetic zinc, we believe that zinc supplementation could improve the zinc status of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ramakrishnan et al, [4] suggests stunting can be prevented through the provision complementary feeding from ages 6 to 24 months of the first children's lives. The study results of Sunaryo [5], showed that were given complementary feeding with the addition of L-glutamine have an increase in length better than the control group and were given complementary feeding without the addition of Lglutamine.…”
Section: Introductionmentioning
confidence: 99%